Prayers for Bobby [videorecording (DVD)] - Mulcahy, Russell, 1953-; Czerny, Henry; Kelley, Ryan, 1986-; Weaver, Sigourney, 1949-; Aarons, Leroy (Distributed by A&E Home Video, 2010)
A Presbyterian wife and mother discovers that her son is gay and seeks to change him through prayer.